Genetics of nitrogen use efficiency and its component traits under nitrogen-rich environment in wheat (Triticum aestivum) - RANJAN, RUMESH; YADAV, RAJBIR (The Indian Journal of Agricultural Sciences, 2021)
Minimizing the footprints of overuse of nitrogen (N) on the ecosystem is the need of an hour. There is little information on the genetic inheritance of NUE and its component traits. The present study was therefore designed to study the genetic behaviour of NUE traits under abundant N supply. Diallel analysis of 21 F1 along with 7 parents was carried out for NUE traits, viz. shoot dry weight (SDW), root dry weight (RDW), maximum root length (MRL), N% in shoot, gram N in shoot (gN) and nitrogen use efficiency (NUE) under high N in hydroponic condition. Analysis of variance revealed significance for both general combining ability (GCA) and specific combining ability (SCA) for all NUE traits indicating the importance of both additive and non-additive gene action for these traits. Baker’s ratio revealed a preponderance of additive genes over non-additive for SDW, RDW and MRLsuggesting thereby effectivity of selection for SDW, RDW, gN, and MRL in the early segregating generation of high GCA lines can improve NUE under high N. Crosses with high SCA effects for SDW, RDW, gN and N% were from the parent combination of high × low GCA effects, whereas for MRL, low × low GCA parents resulted in crosses with high SCA effect indicating the dispersal of favourable alleles in the different parents. Our study indicates the feasibility of improvement of NUE through direct selection for the component traits under N rich environment.